Device for the local radiation of tumor-bearing laboratory rodents - Hübner, Gunnar; Weber, Klaus-Josef; Hartung, Gernot; Zillmann, Uwe (Lab animal, 2010)
Since no standard method for reproducibly irradiating local tumors of laboratory rodents exists, the authors designed a device to accurately irradiate rodent tumors. Laboratory personnel can easily assemble this inexpensive device. The new device delivers highly focused treatment and avoids the need for anesthesia and sedation. It represents an improvement over former improvised procedures done at the authors' institutions, because it allows for more accurate irradiation of rodent tumors. The authors used the device to irradiate single tumors on the left hind legs of 60 mice and 10 rats with a dosage of 7 gray (Gy) ionizing radiation. At time of irradiation, the clinical condition of the animals was very poor, but all animals survived the treatment.
Gesehen am 01.06.2023